2015
DOI: 10.1093/treephys/tpv088
|View full text |Cite
|
Sign up to set email alerts
|

Modification of the tree root electrical capacitance method under laboratory conditions

Abstract: For many years, scientists have been searching for nondestructive methods for the measurement of plant root system parameters. The measurement of electrical capacitance (EC) across the root has been proposed as one such nondestructive method. This article presents a study on the determination of relationships between EC measurement and the shape and size of the electrodes immersed in medium that are used for measurement. Measurement of EC and the parameters characterizing root systems of 1-year-old seedlings o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…The remaining capacitance is thought to be due to the polarization of the epidermal membranes in the root neck and the stem base. The two-dielectric capacitor model assumes that if the soil capacitance is substantially higher than the root capacitance, C R is basically determined by the root system (Rajkai et al 2005;Dietrich et al 2012;Kormanek et al 2016). In the present study, C Soil for the wet substrate proved to be much higher than C R , which met the criteria of this model.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The remaining capacitance is thought to be due to the polarization of the epidermal membranes in the root neck and the stem base. The two-dielectric capacitor model assumes that if the soil capacitance is substantially higher than the root capacitance, C R is basically determined by the root system (Rajkai et al 2005;Dietrich et al 2012;Kormanek et al 2016). In the present study, C Soil for the wet substrate proved to be much higher than C R , which met the criteria of this model.…”
Section: Resultsmentioning
confidence: 99%
“…Likely due to similar reasons, root studies in oilseed plants and young trees showed diurnal patterns in spectral polarization signatures (Weigand and Kemna 2019) and in the magnitude of C R (Ellis et al 2013b). Kormanek et al (2016) found a closer correlation between C R and root size parameters for beech seedlings immersed in hydroponic solution when the root systems were flattened between two flat-plate electrodes and then when the roots were freely arranged inside a cylindrical electrode.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…13. The construction of the electrodes influences the electrical capacitance values of the roots (Kormanek et al, 2016). In order to evaluate the differences within a single measurement, only the values from one set of electrodes need to be used to perform the root system measurements.…”
Section: Root System Electrical Capacitance -A Standardized Methodolomentioning
confidence: 99%
“…For decades, electrical capacitance has been used to estimate the aboveground biomass of herbaceous perennials (Currie et al, 1987) and forest plantations (Lekas et al, 1990), but few root electrical capacitance (REC) studies have focused on clonal woody perennial plants as a model for predicting root biomass. Previous work on the estimation of root biomass using the REC method has primarily focused on hydroponically grown seedlings (Rajkai et al, 2005; Repo et al, 2005; Cao et al, 2011; Dietrich et al, 2012; Cseresnyés et al, 2013; Kormanek and Tomasz, 2015) or a limited number of genotypes (Whitlow et al, 1992; Pitre et al, 2010).…”
mentioning
confidence: 99%